Physicochemical characteristics of andisols and their correlation to potato yield based on land mapping units - Napitupulu, Delima; Rauf, Abdul; Sembiring, Mariani; Marbun, Posma (Comunicata Scientiae, 2024)
The high phosphate retention in andisol soil is often associated with a decrease in potato yield. Additionally, identification of the physical and chemical characteristics of andisols and their correlation to potato yield through soil mapping units (SMUs) is necessary to facilitate field surveys. Therefore, this study aimed to identify the physicochemical characteristics of andisols with a focus on available phosphorus (P) and the correlation to potato production based on SMUs. The experiment was conducted in Karo District, North Sumatra, Indonesia, from July 2022 to February 2023. A descriptive-analytical method was used by overlaying maps of slope, soil types, and altitude until 10 SMUs were selected that were planted with potatoes. Soil physicochemical properties were identified, while Pearson correlation analysis was performed on available-P and potato yield using IBM SPSS software. The results showed that the silt and clay fractions positively correlated with available-P in andisols. All soil physical characteristics were categorized as very weak to weak in supporting potato yield. A total of four SMUs including 1, 5, 8, and 10 were found to have lower available-P and very low to moderate correlations with soil pH, organic-C, C:N ratio, cation exchange capacity (CEC), as well as total-P. Based on the results, potato yield could increase by 1.765 and 0.380 tons ha-1 through the addition of organic-C and C:N ratio in Karo District. Therefore, soil amendment is required as an alternative to improve andisols soil.